Ten-Year Survivorship, Patient-Reported Outcome Measures, and Patient Acceptable Symptom State After Over-the-Top Hamstring Anterior Cruciate Ligament Reconstruction With a Lateral Extra-articular Reconstruction: Analysis of 267 Consecutive Cases. Issue 2 (February 2021) - Grassi, Alberto; Macchiarola, Luca; Lucidi, Gian Andrea; Silvestri, Annamaria; Dal Fabbro, Giacomo; Marcacci, Maurilio; Zaffagnini, Stefano
Background: Long-term patient-reported outcome measures (PROMs) and predictors of success or failure after anterior cruciate ligament (ACL) reconstruction are not fully understood, especially when combined with a lateral extra-articular reconstruction. Purpose: To assess the long-term PROMs, revision rate, and predictors of success or failure after ACL reconstructions using an over-the-top surgical technique with single-bundle hamstring tendon autografts and a lateral extra-articular reconstruction. Study Design: Case series; Level of evidence, 4. Methods: The study cohort consisted of 267 consecutive patients (mean age, 30.7 years) who underwent ACL reconstruction with an over-the-top surgical technique with single-bundle hamstring tendon autografts and a lateral extra-articular augmentation between November 2007 and May 2009. The number of subsequent ACL revisions and reoperations were recorded. Subjective clinical status was assessed with PROMs—specifically, the Knee injury and Osteoarthritis Outcome Score (KOOS), Lysholm, Tegner, and visual analog scale for pain—at a minimum follow-up of 10 years. Results: Overall, 3% of patients underwent ACL revision, with a 10-year survival rate of 96.3%. High sport activity (hazard ratio, 6.9; P = .285) and concomitant meniscal lesion (hazard ratio, 2.6; P = .0487) were predictors of ACL revision or new meniscectomy. The mean ± SD Lysholm score was 94.1 ± 10.8, while that for the visual analog scale for pain was 0.2 ± 0.9 at rest and 2.1 ± 2.6 during activity. KOOS subscale scores were as follows: 95.7 ± 8.1 for Pain, 92.5 ± 10.5 for Symptoms, 98.4 ± 7.4 for Activities of Daily Living, 90.7 ± 17.2 for Sport, and 91.2 ± 17.1 for Quality of Life; respectively, 88%, 99%, 81%, 89%, and 91% of patients achieved the Patient Acceptable Symptom State. Female sex and chondropathy with Outerbridge grade ≥2 were predictors of worse KOOS subscales. Overall, 82% of patients returned to sport, and 57% were still participating at the 10-year evaluation. Conclusion: ACL reconstruction with an over-the-top surgical technique with single-bundle hamstring autografts and a lateral extra-articular reconstruction provided satisfactory results in terms of function, symptoms, sports, and quality of life in 80% to 90% of patients after 10 years. Long-term survivorship was 96%. Sport participation declined from 82% postoperatively to 57% at long-term follow-up. A concomitant medial meniscal lesion was a predictor of higher risk of ACL failure or new meniscal lesion, while advanced chondropathy and female sex were predictors of higher pain, lower function, and poor quality of life scores.